IMMUNOMODULATOR ACTIVITY OF MANGIFERIN FROM MANGO (MANGIFERA INDICA L.) IN CANCER: A SYSTEMATIC REVIEW - AYUNI LUBAKISAR, YACHI QURRATA; FAUZIAH, FITRA; BELLATASIE, REZLIE (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
Cancer is a disease that is causing an increase in mortality all over the world. Cancer treatment is expensive and has a variety of side effects. Natural compound treatment is an attempt to reduce the side effects of cancer therapy. Mangiferin is a natural compound with anticancer and immunomodulatory activity. The immunomodulatory activity of mangiferin from mango (Mangifera indica L.) in cancer was discussed in this article. The literature used in this review was obtained from several databases, including the Cochrane Library, Google Scholar, PubMed, ProQuest, ScienceDirect, and the Wiley Online Library, for articles published over the last ten years. Mangiferin influenced anticancer activity by inhibiting NF-κB, affects the regulation of -catenin, EMT, MMP2, MMP9, LDH, NO, ROS, and inhibits classical macrophages activation. Mangiferin has an immunomodulatory effect that can be developed as a candidate drug for anticancer therapy.